The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1556-4029.2009.01087.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of DNA Forensic Techniques for Identifying Poached Guanacos (Lama guanicoe) in Chilean Patagonia*

Abstract: Guanaco (Lama guanicoe) is a protected and widely distributed ungulate in South America. A poacher, after killing guanacos in Valle Chacabuco, Chilean Patagonia, transported and stored the meat. Samples were retrieved by local police but the suspect argued that the meat was from a horse. Mitochondrial cytochrome b gene (774 pb), 15 loci microsatellites, and SRY gene were used to identify the species, number of animals and their population origin, and the sex of the animals, respectively. Analysis revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
9
0
2
Order By: Relevance
“…El análisis de ADN forense permitió identificar la caza furtiva, el comercio ilegal y el contrabando ilegal de especies amenazadas, entre otros delitos (Iyengar 2014). En lo que respecta a mamíferos neotropicales, se usan distintos marcadores moleculares para identificar carne de guanaco (Lama glama), venado de las pampas (Ozotoceros bezoarticus) y carpincho (H. hydrochaeris) producto de la caza furtiva (Marín et al 2009;Sanches et al 2012). …”
Section: Nardelli and Ji Túnezunclassified
“…El análisis de ADN forense permitió identificar la caza furtiva, el comercio ilegal y el contrabando ilegal de especies amenazadas, entre otros delitos (Iyengar 2014). En lo que respecta a mamíferos neotropicales, se usan distintos marcadores moleculares para identificar carne de guanaco (Lama glama), venado de las pampas (Ozotoceros bezoarticus) y carpincho (H. hydrochaeris) producto de la caza furtiva (Marín et al 2009;Sanches et al 2012). …”
Section: Nardelli and Ji Túnezunclassified
“…Furthermore, the availability of a common set of polymorphic markers in these species allows testing of the population genetic parameters that are required to establish the conservation status of natural populations without needing to develop species-specific markers. We also showed that the differences in allele frequency distributions between these markers have value for forensic cases when species determination is necessary in the absence of phenotypic data (e.g., Marín et al, 2009). These microsatellite markers will be useful for resolving conservation problems related to management programs for these southern Andes deer.…”
Section: Pudu Puda Hippocamelus Bisulcusmentioning
confidence: 99%
“…The possibility of forensic application requires a sound knowledge of the molecular systematics of the involved taxa. The enormous research effort implied must be shared with biologists in general (zoologists, botanists, microbiologists), and in particular with conservationists and other wild life specialists [4,8].…”
Section: Overviewmentioning
confidence: 99%
“…Extension to the forensic examination of non-human DNA lagged behind, but it is now intensively researched and has already provided spectacular and innovative results. This growth can be assessed, for instance, through the number of presentations devoted to non-human DNA in the last International Society for Forensic Genetics Congress (21 out of 317; proceedings soon to be published in Forensic Science International: Genetics Supplement Series) or by browsing the most recent issues of the leading journals in the field [e.g., [2][3][4][5]. Moreover, a comprehensive and authoritative handbook has been recently published [6].…”
Section: Overviewmentioning
confidence: 99%